Tumor necrosis factor alpha has a protective role in a murine model of systemic candidiasis. - Louie, A (1994)
The role of tumor necrosis factor alpha (TNF-alpha) in host defense against systemic Candida albicans infection was evaluated in a murine model of systemic candidiasis in which uniform death occurred between 5 and 6 days after infection. TNF-alpha was first detected at 16 h postinfection and progressively increased thereafter. Peak levels (700 to 900 pg/ml) were measured in mice near death. Administration of 0.5 to 1.0 mg of polyclonal immunoglobulin G (IgG) TNF-alpha antibody (TNF-alpha Ab) to mice 2 h preinfection neutralized serum TNF-alpha for up to 30 h. However, this regimen shortened survival from a mean of 5.5 days for IgG controls to 3.4 days (P = 1.9 x 10(-12)). Semiquantitative cultures of spleen, lung, liver, and kidney conducted at 1, 2, and 3 days postinfection found colony counts of spleen and kidney to be significantly higher for TNF-alpha Ab recipients but only for the first 48 h. Administration of 1.5 and 1.0 mg of TNF-alpha Ab at 2 h before and 48 h after fungal injection, respectively, shortened the mean survival from 4.9 to 2.3 days (P = 5.2 x 10(-8)). This regimen neutralized serum TNF-alpha throughout infection. With this regimen, colony counts of all organs were significantly higher in TNF-alpha Ab recipients at 1, 2, and 3 days postinfection. Histopathologic studies showed an increase in the number and size of C. albicans foci in tissues. Peripheral leukocyte counts and inflammatory response in tissue were similar for TNF-alpha Ab and IgG sham recipients. In vitro, incubation of C. albicans with four to eight times the peak serum levels of TNF-alpha for up to 24 h did not inhibit the rate of germ tube or pseudohypha formation. Thus, TNF-alpha that was produced during infection with C. albicans augmented host resistance against this organism and prolonged survival. The protective effect of TNF-alpha was not mediated by increased leukocytes in blood or tissues nor by a direct anticandidal effect of TNF-alpha. This study suggests that the administration of exogenous TNF-alpha may enhance host resistance against systemic C. albicans infection and may improve host survival.